Finite element analysis of the plantar support for the medial longitudinal arch with flexible flatfoot. - Xiao Long; Xiangyu Du; Chengjie Yuan; Jian Xu; Tao Liu; Yijun Zhang (PLoS ONE)
Purpose The present study is to explore the appropriate plantar support force for its effect on improving the collapse of the medial longitudinal arch with flexible flatfoot. Methods A finite element model with the plantar fascia attenuation was constructed simulating as flexible flatfoot. The appropriate plantar support force was evaluated. The equivalent stress of the articular surface of the joints in the medial longitudinal arch and the maximum principal stress of the ligaments around the ankle were obtained. Results The height fall is smaller when applying 15% of body-weight-bearing force as the plantar support for the medial longitudinal arch compared with 10% of the body-weight-bearing while 20% of body-weight-bearing force is over plantar support. The equivalent stress on the articular surface of each joint is smallest when applying 15% of body-weight-bearing force compared with 10% or 20% of the body-weight-bearing force. The maximum principal stress of the anterior talofibular ligament is decreased while other ligaments increased when the plantar fascia attenuation under loading. The maximum principal stress of the tibiocalcaneal ligament and the posterior tibiotalar ligament are decreasing while other ligaments increased with the force increasing gradually. Conclusions Applying 15% of body-weight-bearing to the sole of the foot can restore the height fall of the medial longitudinal arch, and relieve the equivalent articular stress of the talonavicular joint and the talocalcaneal joint as well as the tension stress of the tibiocalcaneal ligament and the posterior tibiotalar ligament.